Ask questions and get helpful responses.

Trig

sin^4t-cos^4t/sin^2t cos^2t= sec^2t-csc^2t

i have =(sin^2t+cos^2t)(sin^2t+cos^2t)/sin^2tcos^2t
then do i go =(sin^2t+cos^2t)/sin^2tcos^2t

stumped

  1. 👍
  2. 👎
  3. 👁
  4. ℹ️
  5. 🚩
  1. LS = (sin^2 t + cos^2 t)(sin^2 t - cos^2 t)/(sin^2 t cos^2 t)
    = 1(sin^2 t - cos^2 t)/(sin^2 t cos^2 t)
    = sin^2 t/(sin^2 t cos^2 t) - cos^2 t/(sin^2 t cos^2 t)
    = 1/cos^2 t - 1/sin^2 t
    = sec^2 t - csc^2 t
    = RS

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩

Respond to this Question

First Name

Your Response

Still need help? You can ask a new question.